2017
DOI: 10.1515/bejte-2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Firms and the Sequential Adoption of Environmental Corporate Social Responsibility in the Managerial Delegation

Abstract: This article investigates the strategic environmental corporate social responsibility (ECSR) of polluting firms in the presence of eco-firms. When the firms decide to adopt ECSR sequentially within the framework of the managerial incentive design and then face simultaneous price competition, we show that firms will adopt ECSR and purchase abatement goods to mitigate competition if the products are more substitutable, but the late adopter chooses lower ECSR and thus earns higher profit. It can partially explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…Section 5 concludes the paper. 6 It is also well-documented in recent literature that strategic CSR initiatives can increase a firm's profitability (see, e.g., Lambertini and Tampieri, 2015;Liu et al, 2015;Hirose et al, 2017;Leal et al, 2018;Xu and Lee, 2018;Lee and Park, 2019;Garcia et al, 2019). 7 The promotion of CSR has become a top priority in policy agenda in many developed countries such as the United States and in the European Union.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Section 5 concludes the paper. 6 It is also well-documented in recent literature that strategic CSR initiatives can increase a firm's profitability (see, e.g., Lambertini and Tampieri, 2015;Liu et al, 2015;Hirose et al, 2017;Leal et al, 2018;Xu and Lee, 2018;Lee and Park, 2019;Garcia et al, 2019). 7 The promotion of CSR has become a top priority in policy agenda in many developed countries such as the United States and in the European Union.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies show that strategic CSR initiatives can increase a firm's profitability (see, e.g.,Lambertini and Tampieri, 2015;Liu et al, 2015;Hirose et al, 2017;Leal et al, 2018;Xu and Lee, 2018;Lee and Park, 2019;Garcia et al, 2019).…”
mentioning
confidence: 99%
“…However, they confined into the symmetric market configuration of oligopoly competition and revealed that all firms adopt a positive CSR level in the market equilibrium. Hirose et al (2020Hirose et al ( , 2017 and Lee and Park (2019) investigated the strategic environmental corporate social responsibility (ECSR) of polluting firms and showed that firms will adopt ECSR simultaneously or sequentially to mitigate price competition and earn higher profits. In their analysis, however, the economic role of some critical parameters such as product differentiation, economies of scale, multiproduct firms are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more researchers also have paid much attention to CSR and CER [1,2,3,4,5,6]. Qin et al [7] constructed a CER conceptual framework for researchers and proposed a conceptual model for policymakers.…”
Section: Introductionmentioning
confidence: 99%